Diosmin, a citrus fruit-derived phlebotonic bioflavonoid protects rats from chronic kidney disease-induced loss of bone mass and strength without deteriorating the renal function. Issue 4 (4th February 2022) - Sharma, Shivani; Porwal, Konica; Kulkarni, Chirag; Pal, Subhashis; Sihota, Praveer; Kumar, Saroj; Tiwari, Mahesh Chandra; Katekar, Roshan; Kumar, Ashish; Singh, Priya; Rajput, Swati; Guha, Rajdeep; et al.
Abstract : Kidney Disease Improving Global Outcomes (KDIGO) 2017 Clinical Practice Guideline has recommended treatment decisions for patients with chronic kidney disease (CKD) with osteoporosis and/or high risk of fracture. Abstract : Kidney Disease Improving Global Outcomes (KDIGO) 2017 Clinical Practice Guideline has recommended treatment decisions for patients with chronic kidney disease (CKD) with osteoporosis and/or high risk of fracture. Bisphosphonates, the first-line anti-osteoporosis drugs have the concern of worsening kidney functions. Moreover, despite impaired bone formation in CKD patients, teriparatide, the formation-stimulating drug is not recommended. Thus, there is an urgent need for safe and effective treatment of osteoporosis in CKD patients. Here, in CKD rats, we tested the osteoprotective effect of diosmin, a citrus-derived bioflavonoid used as a phlebotonic in chronic venous insufficiency and has a renoprotective effect. CKD was developed by 5/6 th nephrectomy and diosmin at the human equivalent dose (100 mg kg −1 ) did not advance renal failure but reduced blood pressure to the level of sham control. Fibroblast growth factor-23 and parathyroid hormone were increased in CKD and diosmin suppressed both. CKD reduced bone mass and deteriorated the microarchitecture of trabecular bones, and diosmin maintained both to control levels. Bone formation and strength were impaired in the CKD and diosmin maintained these levels to control levels. Nanoindentation of bone showed that diosmin significantly increased tissue hardness over the control. Diosmetin, the metabolic surrogate of diosmin had comparable pharmacokinetic profiles between the control and CKD groups. Furthermore, diosmetin (50 mg kg −1 ) protected against CKD-induced bone loss. These data suggest that diosmin and its metabolic surrogate, diosmetin protect against CKD-induced osteopenia. Since diosmin has no renal adverse effect and protected bone mass and strength in CKD rats, we propose assessing its anti-osteoporosis effect in CKD patients.